Integrated Eco-Friendly Outdoor Cooling System – Case Study of Hot-Humid Climate Countries - Mohammad Bani Khalid (Polish Society of Ecological Engineering (PTIE), 2022)
This research proposed an integrated eco-system for conditioning an outdoor public area (park or sport) in a hot-humid environment. It is accomplished by the use of a dehumidifier control machine driven by renewable solar power; after which air is distributed throughout a ducting system. The system will harvest moisture from the air, utilize it for drinking water production and plants irrigation as well as deliver low temperature, low humidity ratio air for controlling the outdoor air, which results in a comfortable outdoor relative humidity and temperature (24°C, 50% RH). The Integrated Eco-Friendly Cooling System (IEFCS) is a sustainable self-dependent in energy and water sources. It provides a positive impact on the microclimate of the site, assists in night illumination, supplies water for drinking, plant irrigation, and allows people to enjoy a thermally comfortable atmosphere. The advantages include low maintaining cost as well as the possibility to be scaled and implemented anywhere according to the selected location.